LA PRESENCIA DEL CUERPO AUSENTE - Calvario Martínez, Leticia (2023)
Besides its biological particularities, women’s body also means interpretation, culture, religion; it is in fact a socially constructed entity. This essay presents a brief and maybe forced –but needed- comparison of opposing views from Eastern and Western worlds, both of which have put women aside. This comparison seeks to overcome those views that support an allegedly ethical or moral supremacy of one culture over the other. The essay then leads to intellectual works and art representations whose regards witness what remains hidden.